Tradisi Akkammi’ Batara’ di Tritiro Kecamatan Bontotiro Kabupaten Bulukumna Sulawesi Selatan - Ahmad Rasul Suherman; St. Junaeda (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
Akkammi’ batara is a tradition of farming communities in general and the Tritiro community in particular. Akkammi Batarais an activity carried out by farming communities to maintain their gardens, a practice that has been ongoing for a long time until now. This paper aims to understand the process, function, and value of the akkammi' batara tradition. The method used is a descriptive method employing qualitative data. Qualitative data were obtained through observations, interviews with several informants, and data from documents. Observation was conducted by examining how the community's behavior is related to the akkami batara tradition. Observing their behavior starting from the preparation stage, implementation, and related aspects such as specific behaviors at certain times. Including when they leave and how they do it. To complement the data from observations, the researchers also collected field data by conducting interviews with several informants. The informants in this case are farmers who still practice the akkammi’ batara’ tradition to this day, as well as community members who were once actively involved in this tradition. Then, document data is used by the researcher in the form of documents owned by the village government related to data on the area of agricultural land and agricultural yields. This data helps researchers understand the research subject, including understanding the social conditions of the local community. The research results show that the process of akkammi’ batara’ has stages, namely (1) building or repairing the barrier wall or fence, (3) installing traps/sarombe at the edge of the barrier fence, (4) installing tools to repel wild boars and monkeys such as gare’do and lapa-lapa (sound-producing tools), pa’ boang (scarecrows), (5) inserting sappi’ (aromatic pest repellent tools) and scattering fresh leaves or branches (pangompo’) on the outer part of the barrier.